Role of Knowledge Management on the Sustainable Environment: Assessing the Moderating Effect of Innovative Culture - Weina, An; Yanling, Yang (Frontiers in Psychology, 2022)
A sustainable environment has become a necessity at present and has been emphasized immensely due to increased environmental awareness and consequent problems caused by its negligence. The current study intended to determine the role of knowledge management practices in a sustainable environment with the mediating role of environment awareness and green technological use. The study also examined the moderating role of green innovative culture between knowledge management practices and sustainable environment. The data was acquired from 378 managerial level personnel of the construction industry of China through the use of questionnaires. Smart PLS 3.3.3 was used to examine the hypotheses of the study through structural equation modeling (SEM) technique. The study found that knowledge management practice has a relationship with a sustainable environment, environmental awareness, and green technological use. Also, environment awareness has a relationship with a sustainable environment. Moreover, it was found in the study that environment awareness mediated the relationship between knowledge management practices and sustainable environment, but green technological use did not mediate the relationship between knowledge management practices and sustainable environment. Furthermore, green innovative culture moderated the relationship between knowledge management practices and a sustainable environment. Theoretically, the present study contributed in the existing literature by incorporating and investigating the role of knowledge management practices on a sustainable environment. Practically, the paper presented some implications for the management with regard to promoting knowledge management practices and environment awareness within the organization and developing green innovative culture.